Perspectives of Legal Policy on Balancing the Discretionary Provisions of the Tax Code of Ukraine - A. A. Barikova (Bulletin of Kharkiv National University of Internal Affairs)
The purpose of the article is to reveal the key tendencies of legal policy to balance some discretionary provisions of the Tax Code of Ukraine. The author of the article has primarily used the formal and legal special research method. The emphasis has been placed on the fact that the legal institution of discretion in applying the norms of financial law is a complex legal category, which covers the procedural discretion of the subjects of authoritative powers under the norms of substantive (financial) law, as well as administrative and procedural discretion (judicial discretion of administrative justice ).